1998
DOI: 10.1038/sj.ejhg.5200181
|View full text |Cite
|
Sign up to set email alerts
|

Identical mutation in 55% of the ATM alleles in 11 Norwegian AT families: evidence for a founder effect

Abstract: The ATM gene is responsible for the autosomal recessive disorder AtaxiaTelangiectasia (AT). Many different mutations, located all across the gene, have been reported with a predominance of truncating mutations. By using PTT (protein truncation test) a mutation was found in one Norwegian AT family. Sequencing revealed that the mutation affected nucleotides 3245-3247, codon 1082, and changed the sequence from ATC to TGAT, inducing a stop codon downstream at codon 1095 and leading to early truncation of the ATM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
(39 reference statements)
2
36
0
Order By: Relevance
“…Previous studies have shown that specific short tandem repeat (STR) haplotypes observed in ethnic populations can be associated with founder effect mutations, i.e., ''affected haplotypes'' [Uhrhammer et al, 1995;Telatar et al, 1996;Ejima and Saaki, 1998;Laake et al, 1998;Telatar et al, 1998a,b]. Single nucleotide polymorphism (SNP) haplotyping across the region of the ATM gene is of limited informativeness [Bonnen et al, 2000;Thorstenson et al, 2001].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown that specific short tandem repeat (STR) haplotypes observed in ethnic populations can be associated with founder effect mutations, i.e., ''affected haplotypes'' [Uhrhammer et al, 1995;Telatar et al, 1996;Ejima and Saaki, 1998;Laake et al, 1998;Telatar et al, 1998a,b]. Single nucleotide polymorphism (SNP) haplotyping across the region of the ATM gene is of limited informativeness [Bonnen et al, 2000;Thorstenson et al, 2001].…”
Section: Introductionmentioning
confidence: 98%
“…The six mutations screened for are described in Table 1 (Laake et al, 1998(Laake et al, , 2000. Genotyping was performed in microtitre plates by a multiplex PCR in a 25 µl reaction volume containing 50-200 ng leukocyte DNA, 1 × Perkin Elmer buffer I, 4 mM MgCl 2 , 0.15 mM of each of the dNTPs, 0.04 U AmpliTaq, 0.2 µM of each primer, except for the primers ATEX60F and ATEX60R of which 0.6 µM was used.…”
Section: Methodsmentioning
confidence: 99%
“…The six mutations constituted 83% of the disease alleles in the Norwegian AT patients (Laake et al, 1998(Laake et al, , 2000. One single mutation constitutes 57% of the disease alleles.…”
mentioning
confidence: 99%
“…At the end of the follow-up period, conjunctival biopsies were taken from the palpebral fissure and from the fornix of two of the patients (both homozygous for a Norwegian founder mutation) and were compared with biopsies from a 5-year-old Danish AT patient, compound heterozygous for two other ATM mutations. The biopsies were fixated in 4% formalin, cut into 4 lm sections and subjected to in microscope after immunohistochemical staining against Von Willebrand factor, Actin, Neuron specific enolase, Laminin, Fibronectin,Vitronectin, Vimentin, S-100 protein, Type IV collagen, glial fibrillary acid protein (GFAP) and Synaptofysin according to previously described procedures (Bek 1997 Mutation analyses of DNA prepared from peripheral blood cells were performed using several techniques including protein truncating test, denaturing gradient gel electrophoresis, heteroduplex analysis and denaturing high-performance liquid chromatography followed by sequencing, as previously described (Laake et al 1998). The ATM mutation status for seven of the patients has been reported previously (Laake et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Because five patients were homozygous for the Norwegian founder mutation c.3245delATCinsTGAT (Laake et al 1998), we also looked for a possible phenotype ⁄ genotype relationship.…”
Section: Introductionmentioning
confidence: 99%